Clinical and radiographic findings of two dental anomalies of shape in a patient: case report - Costa, Amanda Marinho Chaves (2021)
Dental anomalies, defined as alterations resulting from various etiological factors that act during dental development or acquired during life. Gemination is a dental anomaly that describes an enlarged or unusually shaped tooth that appears to consist of two teeth. Taurodontism is a developmental anomaly that presents as an elongated pulp chamber and short root canals. Patient M.J.C., 61 years old, leucoderma, attended the dental office for oral hygiene assessment. On intraoral examination, it was possible to clinically observe an aspect similar to gemination in tooth 33. Periapical radiography was requested to complement the diagnosis. During radiographic evaluation, it was possible to observe in the region of tooth 46 a decrease in the root canals and an increased pulp chamber, a pathognomonic sign of taurodontism. There was no need for therapeutic intervention regarding the anomalies found. Dentists' knowledge about the clinical and radiographic characteristics of dental anomalies is of fundamental importance for the detection of such anomalies, as well as the most appropriate therapeutic approach for each case.